Experience of Breastfeeding And Exclusive Breastfeeding For Women With Physical Disabilities: Scoping Review - Ririn Ririn; Mufdlilah Mufdlilah; Endang Koni Suryaningsih (Syntax Corporation Indonesia, 2024)
The study aims to investigate the scientific evidence concerning breastfeeding and exclusive breastfeeding experiences among women with physical disabilities. Exclusive breastfeeding entails providing only breast milk to infants from birth to 6 months old, excluding any other food or drinks except medications and vitamins. However, breastfeeding is not halted after exclusive breastfeeding; it continues until the child is two years old. Utilising the scoping review method, the research employed the Population, Concept, and Context (PCC) framework. Six articles meeting the inclusion criteria were identified from a pool of 1,553 articles from PubMed, ScienceDirect, Wiley, and Research Rabbit databases. These articles shed light on the challenges, experiences, barriers, and support systems related to breastfeeding and childcare encountered by women with physical disabilities. The research on breastfeeding experiences among women with physical disabilities reveals both facilitators and barriers. Facilitators include adaptations, peer support, and necessary equipment, while barriers encompass insufficient support, health considerations, and milk production and latching challenges. These findings underscore the importance of tailored support and access to information for women with physical disabilities who aim to breastfeed effectively. Implementing such support mechanisms can contribute to improving breastfeeding rates among this demographic, thus promoting the health and well-being of both mothers and infants while addressing societal attitudes toward disability issues.